2019
DOI: 10.1039/c9cc03797g
|View full text |Cite
|
Sign up to set email alerts
|

Reversible ON/OFF switching of photoluminescence from CsPbX3 quantum dots coated with silica using photochromic diarylethene

Abstract: Highly luminescent silica-coated CsPbX3 quantum dots (QDs) with good photostability were synthesized and coupled with photochromic diarylethene to modulate the QDs’ photoluminescence (PL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Furthermore, photocatalytic reactions could be prevented by modifier coating on the surface of quantum dots, which contribute to the stable ON/ OFF switching. [31] The results indicated that the modulation of the fluorescent switching system with UV/vis lights is completely reversible. At present, the composition of QDs, the modification of the surface and designing the structure of diarylethene are underway to construct the perfect fluorescent switching system.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, photocatalytic reactions could be prevented by modifier coating on the surface of quantum dots, which contribute to the stable ON/ OFF switching. [31] The results indicated that the modulation of the fluorescent switching system with UV/vis lights is completely reversible. At present, the composition of QDs, the modification of the surface and designing the structure of diarylethene are underway to construct the perfect fluorescent switching system.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, direct hollow attack on the quantum dots is also possible. [31] The quantum dots could be modified to improve the emission stability. Furthermore, photocatalytic reactions could be prevented by modifier coating on the surface of quantum dots, which contribute to the stable ON/ OFF switching.…”
Section: Resultsmentioning
confidence: 99%
“…Several known types of the photocontrollable psQDs are based on various photochromes, mostly spiropyrans, azobenzenes and dithienylethenes. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] However, these photochromes are not free from some drawbacks. UV irradiation of spiropyrans gives rise to their open-ring form, merocyanines, which are thermally unstable and in the dark gradually transform back to the closed forms.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior enables the exchange of the native ligands with other adsorption molecules, which is called ligand exchange . Recently, combinations of QDs and functional organic molecules such as chiral molecules, photochromic molecules, π‐conjugated dyes, fullerene‐based molecules, and self‐assembling dyes have been studied to access additional properties and unique behaviors. For example, Jares‐Erijman and co‐workers reported photoswitchable QDs based on the photoisomerization of a diarylethene derivative, in which the emission intensity of the QDs can be controlled by a switch in the energy transfer between the QDs and diarylethene .…”
Section: Introductionmentioning
confidence: 99%